PROTOCOLS OF THE BIOMETRIC IDENTIFICATION SYSTEMS - I. I. Frolov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The survey of protocols of estimation and performance tests of the biometrical systems, and general metrics of the investigation used in case of research of characteristics in biometry are provided. The primary factors of impact on performance criteria of biometrical systems are investigated.